(untitled) (Journal of Applied Learning and Teaching, 2023)
Writing education in the mother tongue is one of the issues that should be emphasized. However, writing motivation does not appear to be a frequently studied topic. The purpose of this study is to examine the effects of wiki-supported, blog-supported and traditional classroom writing activities on the writing motivation of secondary school students. For this purpose, experimental research methods were used. As the procedure, a quasi-experimental design with pretest-posttest control groups was used. Data collection tools were administered to three groups, two experimental and one control group, before and after the experiment. A two-factor ANOVA for the mixed measures procedure was applied to analyze the data. The results showed that Wikis or blogs did not have statistically different effects on writing motivation. The results of the research are important in terms of showing that changing the motivation variable is not possible only with the use of technological tools.